Diagnostic effectiveness of the Sport Mental Health Assessment Tool 1 supplemented with a brief clinical intake interview in a cohort of Polish elite Olympic athletes - Walerianczyk, W.; Krzywanski, J.; Gorgol, J.; Konopka, K.; Kusmierczyk, A.; Lisek, G.; Maleszka, P.; Slawinska, M.; Surala, O.; Wieclaw, G.; Wójcik, K.; Krysztofiak, H. (British Journal of Sports Medicine, 2025)
Objective Several studies have used the Sport Mental Health Assessment Tool 1 (SMHAT-1) among athletes but none have combined SMHAT-1 with a subsequent clinical intake interview. The aim of this study was to evaluate the diagnostic effectiveness of SMHAT-1 supplemented by a brief, in-person clinical intake interview in evaluating the prevalence of mental health concerns in elite athletes.